PREPARATION OF A NOVEL CARBONATED FERMENTED PROBIOTIC DAIRY BEVERAGE USING Lacticaseibacillus rhamnosus AND Candida krusei as CO-CULTURES - M.K. ANJALI*, ATHIRA SURESH, ARCHANA CHANDRAN*, C. ANKITHA ANTO, HELNA PIOUS and S. ARCHANA, (The Journal of Research ANGRAU, 2024)
The study aimed to create a novel carbonated fermented probiotic dairy beverage by employing a co-culture of Lacticaseibacillus rhamnosus ADMH2 and Candida krusei ADMY 29. The resilience of both strains to acidic and bile environment along with gelatinase activity and cell hydrophobicity were assessed to ensure their suitability for probiotic applications. Optimal co-culturing was achieved with a 1:3 ratio of Lacticaseibacillus rhamnosus ADMH2 to Candida krusei ADMY 29 revealing remarkable attributes like protease activity, extracellular polysaccharide production and antimicrobial activity with minimal setting time. This synergistic co-culture was employed to create a carbonated probiotic dairy beverage in a delightful vanilla flavor. The product showed sustained probiotic and yeast counts (above 6.0 logCFU/mL).